Features of the Retina Light Sensitivity in Patients with Chronic Cerebral Ischemia, Depending on the Stage of Discirculatory Encephalopathy with the Use of a Neuropeptide - M. A. Frolov; A. M. Gasankhanova (Oftalʹmologiâ)
Objective. Our study was to examine the degree of the light sensitivity impairment of the retina in patients with chronic cerebral ischemia, as well as to reveal the dynamics of these disorders on the background of the neuropeptide, depending on the stage of vascular encephalopathy.Patients and methods. Comparative analysis of visual function was conducted in 70 persons (140 eyes). Patients were divided into 2 groups, each group is divided into two subgroups. To study the light sensitivity of the retina used automatic computer perimeter Hamphrey Field Analyzer HFA II — I Series (model 610, ZEISS, Germany).Results. As a result of quantifying visual field defects in patients with chronic cerebral ischemia at 2 and 3 tbsp. vascular encephalopathy before treatment received preferential reduction of the light sensitivity of the retina in the temporal halves When comparing manual data with chronic cerebral ischemia patients 2 and 3 stadies vascular encephalopathy control group no significant differences before and after treatment have been identified. However, it is important to note that after 6 months treatment in the same group showed a slight increase in absolute numbers of cattle. In the control group using Cortexin observed reduction in the amount of absolute cattle.Conclusions. The light sensitivity of the retina in patients with chronic cerebral ischemia decreases as the disease progresses, with a primary lesion of the temporal halves of the visual fields. The improvement in the computer perimetry during the treatment, especially in combination with cortexin can be attributed to the normalization of the retina cellular structures, improving the transfer of information and the partial restoration of the disturbed functions, which indicates the relative ischemia is reversible processes, which is effective in patients with stage 2 or 3 vascular encephalopathy.